PENGARUH PIJAT OKSITOSIN TERHADAP KELANCARAN ASI PADA IBU PRIMIPARA (Di Posyandu Balita Desa Segodobancang Kecamatan Tarik Kabupaten Sidoarjo) - Umy Naziroh; Inayatur Rosyidah; Iva Millia H.R Millia H.R (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2019)
The inability of secretion of breastfeeding was a problem which was experienced by breastfeeding mothers. It was needed non pharmacology effort namely massage of oxytocyn. The purpose of this study was to analyze the effect of oxytocyn massage to the smoothness of breastfeeding in primiparous mother in the Village of Segodobancang Districts of Tarik, Sidoarjo regency. This research design was one group pre test post test design. The population in this study were all primiparous mothers who experienced insufficiency of breastfeeding expenditure in the village of Segodobancang sub- districts of Tarik, Sidoarjo regency a number of 27 mothers. The sample amounted to 25 mothers with simple random sampling technique. The independent variable was the oxytocyn massage and the dependent variable was the fluency of mother's milk in primiparous. The data collection used observation sheet and questionnaire. The technique of data processing used editing, coding, scoring, tabulating and its statistical test used the statistical test of wilcoxon rank test. The results of this study were obtained from 25 respondents, before Oxytocyn massage was conducted, most of the respondents of their fluidity breastfeeding expenditure of 0 (0%), smoothly enough were 8 mothers (32%), less fluent were 17 mothers (68%), after being conducted oxytocyn massage most of their fluidity breastfeeding expenditure were 25 mothers (100%). The wilcoxon statistical test showed that’s the value of p = 0,000 <a (0.05) so that H1 was accepted. The conclusion was that there’s an effect of oxytocyn massage to the smoothness of breastfeeding in the Toddler Posyandu of Segodobancang village, sub-districts of Tarik, Sidoarjo regency.